2017
DOI: 10.1093/ve/vex002
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetics of the global population of potato virus Y and its necrogenic recombinants

Abstract: Potato virus Y (PVY) is a major pathogen of potatoes and other solanaceous crops worldwide. It is most closely related to potyviruses first or only found in the Americas, and it almost certainly originated in the Andes, where its hosts were domesticated. We have inferred the phylogeny of the published genomic sequences of 240 PVY isolates collected since 1938 worldwide, but not the Andes. All fall into five groupings, which mostly, but not exclusively, correspond with groupings already devised using biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 89 publications
6
49
0
Order By: Relevance
“…Thus, the RdRp or the helicase proteins are probably most appropriate for inferring the phylogeny of the potyvirids. A maximum likelihood (ML) phylogeny of 166 potyvirids, calculated using the same methods as [29][30][31], from the protein sequences encoded by the RdRp regions of all genomes with GenBank Reference Sequence Accession Codes (July 2019), together with any others that had unique names. The most closely related non-potyvirid, bufivirus UC1, is included as an outlier.…”
Section: The Origins Of the Potyviridaementioning
confidence: 99%
“…Thus, the RdRp or the helicase proteins are probably most appropriate for inferring the phylogeny of the potyvirids. A maximum likelihood (ML) phylogeny of 166 potyvirids, calculated using the same methods as [29][30][31], from the protein sequences encoded by the RdRp regions of all genomes with GenBank Reference Sequence Accession Codes (July 2019), together with any others that had unique names. The most closely related non-potyvirid, bufivirus UC1, is included as an outlier.…”
Section: The Origins Of the Potyviridaementioning
confidence: 99%
“…Table 3). Since recombination confounds phylogenetic analysis (Gibbs et al, 2017), the recombinant sequence (MG885794) was discarded from the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, Giolitti et al (2010) showed that SCMoV might be a pioneer species descending from PVY, which acquired infectivity to other plant families. Interestingly, the origins and/or first records of some potyviruses, including members of the PVY group, were in South America (Gibbs and Ohshima, 2010; Gibbs et al, 2017). PVY is a major pathogen of potatoes and other solanaceous crops worldwide that infects various plant species, including Lactuca serriola , a species of the Asteraceae family (Kaliciak and Syller, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potato virus Y (PVY) is the type-species of genus Potyvirus, which is a member of Potyviridae family (Pringle, 1999;Abdel-Shafi et al, 2017;Dupuis;Gibbs et al, 2017). This genus of Potyvirus forms one of the largest and most economically important groups of plant viruses.…”
Section: Introductionmentioning
confidence: 99%